(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Modern information systems play an important role in every field, including business, health, education, and government. They help to automate the processes of data collection, storage and processing. However, the effective operation and security of information systems depends on cyber security. Cyber security, in turn, is a set of measures necessary to ensure the protection of information systems, the confidentiality and integrity of information. This article provides an overview of information systems and their cyber security requirements on the example of foreign experiences.